DEVELOPMENT OF CULTURAL INTELLIGENCE IN IMPROVING WORK BEHAVIOR INNOVATIVE - Novita, Dina; Marpaung, Daulat (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Innovative work behavior is critical to organizational success. An individual’s competence to understand the cultural preferences, values, norms, beliefs, language, and differences of other members of the organization is important in a culturally diverse workplace. This study aims to determine the effect of cultural intelligence on innovative work behavior through the mediation of work engagement. This study involved 100 employees of the multinational company PT. Unilever Tbk operating in Surabaya. Data collection in this study was carried out using a questionnaire, while the analytical tool used was structural equation modeling (SEM). Based on the results of the study, it is known that cultural intelligence influences innovative work behavior, work involvement has a role as a partial mediation of the relationship between cultural intelligence and innovative work behavior. Employees with high cultural intelligence have a relatively higher level of work involved and tend to display innovative work behavior, s that companies are expected to develop a tolerance for cultural diversity to be able to accept differences, as well as employees must have a broad acceptance of cultural differences, so that with knowledge culture of being able to collaborate with other employees to be active and innovative at work.